(Im)perfect celebrations by intergenerational hostesses: Katherine Mansfield’s “The garden party” and Virginia Woolf’s Mrs. Dalloway - Cortés Vieco, Francisco José (International Journal of English Studies, 2020)
Katherine Mansfield and Virginia Woolf nourished a peculiar stream of parallel foreignness and kinship with each other as coetaneous writers. This article explores the likenesses and dialogues between Mansfield’s story “The Garden Party” and Woolf’s Mrs. Dalloway to detect and depict how bourgeois women, like Laura Sheridan and Clarissa Dalloway, albeit from two different generations, are indoctrinated by social etiquette, class consciousness and the prevailing archetype of domestic femininity inherited from Victorian times. Integrated into their compulsory roles as angelic daughters and wives, Laura and Clarissa gladly perform the role of the hostess to organise (im)perfect parties at home until death knocks at the door. Paradoxically that uninvited guest precipitates escapades of self-discovery and mental emancipation, leading to transient or enduring transformations in the lives of these two women.